2000
DOI: 10.1097/00132586-200012000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron/Dexamethasone Combination for the Prevention of Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy

Abstract: complete response, defined as no PONV and no need for another rescue antiemetic, during 0-3 h after an-Dexamethasone decreases chemotherapy-induced aesthesia was 83% with granisetron and 98% with emesis when added to an antiemetic regimen. This granisetron plus dexamethasone, respectively (P= study was undertaken to evaluate the efficacy of gran-0.008); the corresponding incidence during 3-24 h after isetron/dexamethasone combination for preventing anaesthesia was 83% and 98% (P=0.008). No clinically postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 2 publications
3
45
0
Order By: Relevance
“…Furthermore, Fujii et al have shown the benefit of using the combination of granisetron and dexamethasone for preventing PONV after LC. In their prospective double-blinded study of 120 patients, 83% of patients had no PONV and no rescue antiemetic requirement during the first three postoperative hours with granisetron alone, but increased to 98% when combined with dexamethasone [5][6][7]. In our study, the combination of ondansetron, dexamethasone, and metoclopramide revealed a comparable statistical difference in postoperative nausea rating, predominately among the female population.…”
Section: Meansupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, Fujii et al have shown the benefit of using the combination of granisetron and dexamethasone for preventing PONV after LC. In their prospective double-blinded study of 120 patients, 83% of patients had no PONV and no rescue antiemetic requirement during the first three postoperative hours with granisetron alone, but increased to 98% when combined with dexamethasone [5][6][7]. In our study, the combination of ondansetron, dexamethasone, and metoclopramide revealed a comparable statistical difference in postoperative nausea rating, predominately among the female population.…”
Section: Meansupporting
confidence: 59%
“…Fiorillo also show that 91 of 149 patients (61%) remained less than 24 hours within the hospital. However, the 58 patients that required an overnight stay due to postoperative pain, nausea and vomiting, which suggests that better perioperative regimens are needed to prevent overnight hospitalizations [5]. In the current trial, the overall LOS in the control group was 12.88 hours versus 9.85 hours in the intervention group (p = 0.0006).…”
Section: Meanmentioning
confidence: 65%
“…The dose of dexamethasone used, 8 mg, was based on previous reports shown to decrease PONV when used as an antiemetic regimen [2,6,7,9,15]. The doses of ondansetron 4 mg and granisetron 3 mg were also in accordance with the previous studies in which they were used as antiemetics for PONV [3,6,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have shown that glucocorticoids are equal to or better than other drugs such as metoclopramide, ondansetron, or droperidol in preventing nausea and vomiting associated with chemotherapy [13]. Recently, dexamethasone has been shown to be effective in reducing nausea and vomiting after open and laparoscopic surgical procedures [2,3,5,6,7,9,17,18]. Several randomized controlled trials have shown that dexamethasone alone [2,7,15,17,18] or in combination with other drugs (granisetron, ondansetron, tropisetron, dolasetron) [3,5,6,9] is effective in reducing postoperative nausea and vomiting and antiemetic requirement after laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation